ORGANIZATIONAL AND ECONOMIC MEASURES OF PROMOTING INVESTMENT ACTIVITY OF ENTERPRISES - N. Karachyna (Економіка розвитку, 2013)
Based on the task of providing stable supply of investment resources the current situation with the flow of investments into enterprises is considered in the paper, the main problems faced by investors are determined and summarized. Strategic opportunities and ways to facilitate investment activities of enterprises in the light of such basic factors as the use of leasing, size and availability of tax credits are identified. Particularly the procedure of tax arrest and sale of tax property is suggested to be canceled, companies are encouraged to increase the declared income and number of employees in order to use company rules of the Tax Code and apply the 0 % rate for income tax. Realizing the shortage of funds in businesses the authors suggest to change the amount of fees for notarial registration of contracts and state dues of 5 % of a contract value to a constant amount. The authors consider it inappropriate and suggest to review the bank demands for companies that receive foreign currency loans, are engaged in export activities, provide information about the environmental and social standards compliance. The circumstances under which businesses can credit each other and the amount of loan can rise unilaterally are singled out. A number of recommendations to be used in leasing contracts are made.Since these steps should have a comprehensive approach to the regulation of company conditions the authors offer to show them as the basic policy and target blocks and the overall system activities to promote the investments.